Reflections on ELT pedagogy : Functioning and communicating in English - Cavalheiro, Lili (2017)
Globalization and multicultural communicative settings have contributed to the expansion of English as the main international language and as a result, English as a Lingua Franca use has been on the rise. Considering this situation, the concept of English as a Foreign Language seems to no longer fulfill the needs of our multicultural society in constant transformation. Accordingly, research in English pedagogy has also shifted from Standard English and grammatical correctness approaches, to communicative competence and communicative effectiveness. Nowadays, learning English is a two-way process in which the goal for many (depending on the students and aims) is to achieve intercultural communicative competence in order to acquire the knowledge, skills, attitudes and critical cultural awareness necessary to communicate. The essential shift has therefore been from an approach aimed at achieving fixed “forms”, to a method in which we learn how to “function” accordingly with the language in variable contexts.